2023
DOI: 10.1017/s095026882300050x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B in Africa Collaborative Network: cohort profile and analysis of baseline data

Abstract: Approximately 80 million people live with chronic hepatitis B virus (HBV) infection in the WHO Africa Region. The natural history of HBV infection in this population is poorly characterized, and may differ from patterns observed elsewhere due to differences in prevailing genotypes, environmental exposures, co-infections, and host genetics. Existing research is largely drawn from small, singlecentre cohorts, with limited follow-up time. The Hepatitis B in Africa collaborative network (HEPSANET) was established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…These findings align with previous research findings from endemic areas to hepatitis B. Data from the African Multi-Country Research Collaborative Network showed that males make up more than 60% of patients registered in 13 cohorts of hepatitis clinics across 8 African Open Journal of Gastroenterology countries [19]. Furthermore, a community-based cross-sectional study in Zambia, reported that males had 2 -5 times higher eligibility for antiviral treatment [12] compared to females.…”
Section: Discussionsupporting
confidence: 88%
“…These findings align with previous research findings from endemic areas to hepatitis B. Data from the African Multi-Country Research Collaborative Network showed that males make up more than 60% of patients registered in 13 cohorts of hepatitis clinics across 8 African Open Journal of Gastroenterology countries [19]. Furthermore, a community-based cross-sectional study in Zambia, reported that males had 2 -5 times higher eligibility for antiviral treatment [12] compared to females.…”
Section: Discussionsupporting
confidence: 88%
“…The patient group mainly consisted of older males with normal ALT and AFP levels. The majority of patients had HBeAg negative chronic infection (inactive carriers), which is commonly seen in patients with chronic HBV infection in African regions [ 33 , 34 ] and other parts of the world [ 35 ]. This HBV profile was generally associated with a positive prognosis and low severity of liver disease [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used the cross-sectional database established by the HEPSANET consortium. 17 , 19 Briefly, a systematic review was conducted to identify observational studies focusing on individuals with chronic HBV infection in SSA. These studies were at least required to provide data on fibrosis stage and platelet count.…”
Section: Methodsmentioning
confidence: 99%
“…All authors agreed to share data, and a total of 13 distinct cohorts from 8 countries participated in this database. 17 From this database, we included participants meeting the following criteria for this analysis: i) age 18 years or older, ii) have not commenced antiviral therapy; iii) fibrosis stage determined through a valid liver stiffness measurement using transient elastography 20 or liver histopathology; and iv) having data on ALT, AST, platelet count, and HBV DNA levels. We excluded participants if they met any of the following conditions: presence of metabolic disorders (e.g., diabetes, liver steatosis, hypertension, hyperlipidemia); co-infection with HIV, HCV, hepatitis D virus (HDV), or schistosomiasis; missing data pertaining to age or sex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation